Effect of application of organic and inorganic fertilizer on soybean yield in lowland Vertisols - Henny Kuntyastuti; S Sutrisno; Sri Ayu Dwi Lestari (Journal of Degraded and Mining Lands Management, 2020)
Application of organic fertilizer can maintain and improve physical, chemical, and biological soil fertility and plant productivity. However, the use of manure requires a long time and a relatively large amount to have a positive impact on the soil and plants. In this regard, a study was carried out to evaluate the effect of the application of organic fertilizer and NPK inorganic fertilizer on soybean in lowland Vertisol. The study was conducted in lowland Vertisols in Ngawi and Madiun. The experiment used a randomized block design with three replications, with combination treatments of cow and chicken manure, Santap NM1 and NM2 fertilizer, and Phonska. The soybean seed used in this research was Local Central Java/Sinabung-1036 soybean line. The results showed that in lowland Vertisol of Ngawi which is rich in P element, application of 5,000 kg of cow manure/ha, 3,000 kg of chicken manure/ha, 1,500-2,500 kg/ha Santap NM1 and NM2 fertilizers, and 300 kg of Phonska/ha is not required. The yield of Local Central Java/Sinabung-1036 soybean line reached 1.95 t/ha. The lowland Vertisol of Madiun which has poor P element requires the addition of 5,000 kg of cow manure/ha, 1,500-2,500 kg/ha of Santap NM2 fertilizer, and 150 kg of Phonska/ha to increase soybean yield by 21-27% (0.42-0.55 t/ha). The quality and productivity of soil and crop cultivation in sustainable agriculture can be maintained by alternative recommendations for the use of organic and inorganic fertilizer inputs.